Faktory, limitiruyushchie progress sportivnykh rezul'tatov i kvalifikatsii futbolistov - Visochin, Yu. V.; Denisenko, Ju. P. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this research was revealing the factors, predetermining or limiting the growth of sports qualification in football. Some series of experiments were carried out. More than 300 football players of various qualification participated in them. The analysis of results of researches had found out the high reliable distinction of Central Nervous System (CNS) on all parameters describing a functional condition. Increased irritability of CNS, weakness of the brake control and low speed of the voluntary relaxation of muscles are primary factors limiting growth of sports results and qualification of the football players at the stages of maximum sports skill. The elimination of the limiting factors by use of special resources and methods psychological, relaxational and functional training can essentially raise the efficiency of training process of the highly skilled football players.